ChipSats for Planetary Exploration: Dynamics and Aerothermal Modeling of Atmospheric Entry and Dispersion - Umansky-Castro, Joshua S.; Yap, Kimberly G.; Peck, Mason A. (Frontiers in Astronomy and Space Sciences, 2021)
This paper presents an orbit-to-ground model for the atmospheric entry of ChipSats, gram-scale spacecraft that offer unique advantages over their conventionally larger counterparts. ChipSats may prove particularly useful for in-situ measurements in the upper atmosphere, where spatially and temporally varying phenomena are especially difficult to characterize. Globally distributed ChipSats would enable datasets of unprecedented detail, assuming they could survive. The model presented is used to assess the survival and dispersion of a swarm of ChipSats when deployed over the Earth, Moon, Mars, and Titan. These planetary exploration case studies focus on the Monarch, the newest-generation ChipSat developed at Cornell University, in order to evaluate technology readiness for such missions. A parametric study is then conducted to inform future ChipSat design, highlighting the role of the ballistic coefficient in both peak entry temperature and mission duration.